(3ebGdI aj Cfg jMH Cf jchf GdWHjH GdaGVd ajdShakGs - (3LGdjfhSs ((3Nda Hf CHj GdQHjY GdCfOdSi s)
(3ChdgG (B:s
(3bGd Efg bO JYQV dcKjQ ef GdCWHGA eKd GdPi YQV dcKjQ ef GdeUGQYjf GdPjf jMHhf Cf jfJSHhG Edi hge dGjaYdhf SHHkG ef GdCSHGH GdJi jfHZi Cf jaYdhgG MJi jUdhG HgG Edi Pdc s
(3BNQgG (B:s
(3hfMf EP aYdfG Pdc de jefYfG eGfY ef Cf fUjQ CfOGOkG dHbQGW Hd CaVd efg EPG fMf JYdefG efg LejY eG CJjJg ai cJHg Ydi eG jfHZi JeJ ebGdI LGdjfhS s
(3Vef eLehY , JQJjHgG (B: (3GdebGdI GdSGOSIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs